2010
DOI: 10.1111/j.1439-0396.2010.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt reduces the Δ9-desaturase index of sow milk

Abstract: The main objective of this study was to examine if cobalt (Co) reduces Δ(9) -desaturase indices in milk and blood lipids in sows. The experimental design consisted of a repeated measurement consisting of a pre-treatment period of a minimum of 9 days, a treatment period of 5 days and a post-treatment period of 6 days. Experimental animals consisted of 10 lactating sows; five sows had an intramuscular injection of 59 mg Co diluted in 5 ml 0.9% saline solution twice a day, whereas the other five had an intramuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Administration of Co has been demonstrated to decrease milk concentration of FA containing a cis-9 double bond in lactating cows (Shingfield et al, 2008;Taugbøl et al, 2008;Karlengen et al, 2012) and sows (Karlengen et al, 2011) but no reports exist for sheep. Preliminary assays conducted by the current authors suggested that changes in ovine milk FA composition to Co were less pronounced than that reported in cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of Co has been demonstrated to decrease milk concentration of FA containing a cis-9 double bond in lactating cows (Shingfield et al, 2008;Taugbøl et al, 2008;Karlengen et al, 2012) and sows (Karlengen et al, 2011) but no reports exist for sheep. Preliminary assays conducted by the current authors suggested that changes in ovine milk FA composition to Co were less pronounced than that reported in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies discovered rather serendipitously that administration of Co in the form of Co-EDTA (Shingfield et al, 2008) or Co acetate (Taugbøl et al, 2008;Karlengen et al, 2012) to lactating cows decreased milk fat concentrations of FA containing a cis-9 double bond. Intramuscular injections of Co acetate were also reported to induce similar changes in milk fat composi-tion in lactating sows (Karlengen et al, 2011). However, no reports exist on the effects of Co on milk fat composition in sheep.…”
Section: Introductionmentioning
confidence: 94%
“…Based on the potential benefits to human health, there is considerable interest in altering the composition of ruminant milk fat, with decreases in 12:0, 14:0, and 16:0 and increases in cis-9 18:1 and cis-9,trans-11 CLA considered targets (1). Synthesis of milk fat in ruminants involves a highly regulated 8 Abbreviations used: ACACA, acetyl-CoA carboxylase a; ACSL, acyl-CoA synthetase long-chain family member; AGPAT, 1-acylglycerol-3-phosphate O-acyltransferase; AV, arterial-venous concentration; BHBA, b-hydroxybutyrate; C0, 0 g Co/d; C15, 1.5 g Co/d; C30, 3.0 g Co/d; C45, 4.5 g Co/d; CD36, CD36 molecule (thrombospondin receptor); Co-EDTA, lithium salt of cobalt EDTA; CYB5, cytochrome b 5 ; DGAT, diacylglycerol O-acyltransferase; FABP, FA-binding protein; FADS, FA desaturase; FASN, FA synthase; GPAM, glycerol-3-phosphate acyltransferase, mitochondrial; INSIG, insulin-induced gene; LPIN, lipin; LPL, lipoprotein lipase; MFG, milk fat globule; PPARG, peroxisome proliferator-activated receptor g; RPS15, ribosomal protein S15; SCAP, SREBF chaperone; SCD, stearoyl-coenzyme A desaturase; SREBF, sterol regulatory element-binding transcription factor; SREBP, sterol regulatory element-binding protein; THRSP, thyroid hormone responsive; UXT, ubiquitously expressed, prefoldin-like chaperone; VFA, volatile FA.…”
Section: Introductionmentioning
confidence: 99%
“…and coordinated uptake of FAs from the peripheral circulation and the synthesis of FAs de novo in the mammary gland (2). Several preformed and de novo synthesized FAs serve as substrates for stearoyl-CoA desaturase (SCD) 8 , with the desaturation products formed used in the synthesis of milk fat TG. Activity of the mammary SCD enzyme is responsible for the majority of cis-9,trans-11 CLA and a substantial proportion of cis-9 18:1 secreted in milk (1).…”
Section: Introductionmentioning
confidence: 99%
“…Excess iron (Fe) increases the SCD gene expression in the liver of mouse (Pigeon et al., 2001), while zinc (Zn) decreases the gene expression in the liver of rats (Sun et al., 2007). Recently, studies have demonstrated that Cobalt (Co) reduces the proportion of stearoyl‐CoA desaturated fatty acids in milk when supplied in large amounts in both dairy cows (Shingfield et al., 2008; Taugbøl et al., 2008, 2010) and lactating sows (Karlengen et al., In press). However, the regulation of SCD is complex; no conclusions can be drawn from these past experiments to determine whether Co depresses SCD at a transcriptional or post‐transcriptional level or both.…”
Section: Introductionmentioning
confidence: 99%